The development of the maturity model to evaluate the smart SMEs 4.0 readiness - Nilubon Chonsawat (2019)
© IEOM Society International. The first industrial 4.0 revolution was an announcement by Germany in 2013. That the advanced technology has applied in the industrial sectors such as the Internet of thing, Cyber-Physical System, Big Data and Cloud Computing. Especially in the field of Small and Medium Enterprise (SMEs) size, which is the mainstay of the economic development. However, SMEs are still lacking the knowledge and understanding to adopt the technology properly into the smart SMEs. In this research was defined the maturity model to assess the Smart SMEs readiness. First, the paper was reviewed and discussed the exit of assessment and maturity model. Then defined the importance of the dimension of the concept of Industry 4.0. The survey based on a case study was validated by the model. Overall the paper was present the 5 Dimension and 43 Sub-Dimension. The main important dimension is Manufacturing and Operations, People Capability, Technology Driven Process, Digital Support and the last important is Business and Organization Strategy. After that, the Maturity Model of Dimension in the Industry 4.0 transformation was tested by the real company aspects into the measuring. The result shows the Model was clear, easy to understands and can improve the organization by individual case.